Helping Adult Chinese EFL Learners Acquiring Vocabulary Via a Context-Based Approach - Yu Shuying (HOW, 2016)
A very important way of coming across new vocabulary in context is through extensive reading. Developing strategies for handling unknown words has been one of the objectives of English teaching classes. There are different ways to achieve this objective. In China the usual practice is that the class reads only passages where every word is known before, or is allowed to consult a bilingual dictionary or a teacher for meaning or the definitions of every new word if there is a new word in the text. The drawbacks of this approach are obvious. Too much dictionary work can kill all interest in reading and even interfere with comprehension because the reader is so concerned with individual words that he is less aware of the context which gives them meaning. It also results in very slow and inefficient reading (Wallace, 1982: 113).